FAKTORFAKTOR YANG MEMENGARUHI NEUROPATI PERIFER TERKAIT HIV DI MANADO - Deivy Cirayow,* Arthur Hendrik Philips Mawuntu,* Herlyani Khosama* (NEURONA, 2018)
INTRODUCTION THERE ARE SEVERAL SOCIODEMOGRAPHIC AND CLINICAL FACTORS THAT INFLUENCE THE DEVELOPMENT OF HIV ASSOCIATED PERIPHERAL NEUROPATHY HIVPN MANADO HAS DIFFERENT SOCIODEMOGRAPHIC AND CLINICAL CHARACTERISTICS FROM OTHER REGIONS HOWEVER THE PERCENTAGE OF HIVPN AND ITS INFLUENCING FACTORS ARE UNKNOWN